2020
DOI: 10.3390/fluids5040218
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Cavitation Effects on the Vortex Shedding from a Hydrofoil with Blunt Trailing Edge

Abstract: Vortex cavitation can appear in the wake flow of hydrofoils, inducing unwanted consequences such as vibrations or unstable behaviors in hydraulic machinery and systems. To investigate the cavitation effects on hydrofoil vortex shedding, a numerical investigation of the flow around a 2D NACA0009 with a blunt trailing edge at free caviation conditions and at two degrees of cavitation developments has been carried out by means of the Zwart cavitation model and the LES WALE turbulence model which permits predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…It can be observed that the vertical red line is displaced downstream when the cavitation number is reduced, indicating that the vortex shedding formation location takes place further downstream in these conditions. This phenomenon was also observed by Chen et al [22] and Ausoni et al [6].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…It can be observed that the vertical red line is displaced downstream when the cavitation number is reduced, indicating that the vortex shedding formation location takes place further downstream in these conditions. This phenomenon was also observed by Chen et al [22] and Ausoni et al [6].…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the horizontal red line descends along the vertical Y-axis when wake cavitation occurs, indicating a decrease of the vortex shedding formation location, which results in an increase in the vortices alignment. Again, Chen et al [22] also observed this phenomenon numerically. More specifically, Figure 10 shows the streamwise velocity distribution with vertical and horizontal red lines, added on the contour plots, pointing to the locations where vortices occurred.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations